RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS ESTIMATION OF GATIFLOXACIN AND FLURBIPROFEN IN PHARMACEUTICAL DOSAGE FORM - Siddiraju, Sridhar; Kavitha, Rayala; Sudhakar, Muvvala (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The aim of this work was focused on to develop and validate an accurate, simple reverse phase high-performance liquid chromatography (HPLC) method for simultaneous estimation of gatifloxacin and flurbiprofen in pharmaceutical dosage form. Methods: The chromatographic separation was performed on a kromosil C18 column (150 mm × 4.6 mm × 5 μ), with a mobile phase comprising of a mixture of potassium dihydrogen orthophosphate and acetonitrile (48:52) and pH is adjusted to 7.5 by adding 1 ml triethylamine, at a flow rate of 0.8 ml/minutes, with detection at 245 nm. Results: Retention times of gatifloxacin and flurbiprofen were found to be 2.3 minutes and 5.6 minutes respectively. The developed method was validated according to ICH guidelines. Linearity of gatifloxacin was found to be in the range of 75-450 μg/ml and that for flurbiprofen was found to be in the range of 7.5-45 μg/ml. The percentage recoveries for both drugs were found in the range of 99-101%. The limit of detection and limit of quantification values for gatifloxacin were found to be 0.38 and 1.16 μg/ml and that for flurbiprofen were found to be 0.05 and 0.14 μg/ml, respectively. Conclusion: The proposed HPLC method is simple, rapid, isocratic, specific, accurate and precise. Hence, this method can be recommended for the estimation of gatifloxacin and flurbiprofen in pharmaceutical dosage form. Keywords: Gatifloxacin, Flurbiprofen, Reverse phase high performance liquid chromatography method, Validation.